2017
DOI: 10.1017/s0376892917000133
|View full text |Cite
|
Sign up to set email alerts
|

Wildlife species preferences differ among children in continental and island locations

Abstract: SUMMARYEfforts to prioritize wildlife for conservation benefit from an understanding of public preferences for particular species, yet no studies have integrated species preferences with key attributes of the conservation landscape such as whether species occur on islands (where invasive exotics are the primary extinction threat) or continents (where land use change is the primary extinction threat). In this paper, we compare wildlife species preferences among children from a continental location (North Caroli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 69 publications
(109 reference statements)
2
8
0
Order By: Relevance
“…The youth in Bahía de Jiquilisco listed turtles among their favourite species far more often than children and youth in areas with relatively large sea turtle populations, such as the Bahamas (Shapiro et al 2017). This finding may be explained by the high percentage of our sample that participated in ICAPO's activities, whose programming focused on hawksbill turtle conservation, and supports other research that demonstrates pedagogical hands-on activities improve students' knowledge and attitudes towards biodiversity, especially reptiles and amphibians (Ballouard et al 2012, Sousa et al 2016.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The youth in Bahía de Jiquilisco listed turtles among their favourite species far more often than children and youth in areas with relatively large sea turtle populations, such as the Bahamas (Shapiro et al 2017). This finding may be explained by the high percentage of our sample that participated in ICAPO's activities, whose programming focused on hawksbill turtle conservation, and supports other research that demonstrates pedagogical hands-on activities improve students' knowledge and attitudes towards biodiversity, especially reptiles and amphibians (Ballouard et al 2012, Sousa et al 2016.…”
Section: Discussionsupporting
confidence: 80%
“…For youth wildlife preferences, we assigned each species listed by students to 1 of 26 taxonomic categories. A single species received its own category if it occurred in at least 10% of surveys for favourite species overall and favourite species in El Salvador (Shapiro et al 2017). For all other species, we used relevant taxonomic categories (e.g., amphibian).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This inevitably reduces native species richness, and indeed all species richness in highly urbanized areas, but in suburban areas it increases introduced species richness (McKinney 2008). Densely populated cities have long been hubs for IAS transportation (Hulme 2009), and urbanized populations tend to associate nature firstly with introduced species (Shapiro et al in press). Trade in pets and ornamental plants is focused around urban areas, which are source points for IASs into surrounding landscapes (Carrete & Tella 2008; Hulme 2015), and air and sea ports of urban areas on islands are the primary entry points for IAS incursions.…”
Section: Interactionsmentioning
confidence: 99%
“…Further, the distinction between species could be gender differentiated. Olive (2012) found that her sample of U.S. women were more concerned about the viability of a tortoise than a snake's viability and Shapiro et al (2017) found that boys in the US and Bahamas preferred fish and lizards while girls from those countries preferred rabbits and horses. Thus, the lack of generalizable evidence implies that Noah would not know how to factor gender differentiation into his assessment of the value of particular species.…”
Section: Changes In Total Economic Value (∆Tev I )mentioning
confidence: 99%